Coexistence of multiple strains of porcine parvovirus 2 in pig farms. (July 2014) - Saekhow, Prayuth; Mawatari, Takahiro; Ikeda, Hidetoshi
Abstract The porcine parvovirus 2 (PPV2) genome was first identified in 2001 in Myanmar. Recently, the PPV2 genome has been found in several other countries. In this study, the prevalence of PPV2 in Japanese domestic pigs was investigated and found to be 58% (69/120) in healthy domestic pigs and 100% (69/69) in sick domestic pigs. Sequencing and phylogenetic analysis of the PCR products of the VP1 gene and an almost full length PPV2 clone indicated that diverged PPV2 strains exist in Japan. Clearly distinct strains of PPV2 were detected in 7 of the 10 pig farms.